Database security system with multi entrances - Mohd Nurfajren, Mat Isa (2009)
Database security system is a simple system that stores the user information in high secured location such as research laboratory. Only authorized users are allowed to enter the room by using a simple keypad as an entry point. The information of the user will be displayed and store in the PC using Visual Basic software. The information may include user name's, date and time entrance. Microcontroller MC68HC1 lAl is used as its processor to control the whole system operation. By using Electromagnetic Door Lock (EDC) the door will be unlocked automatically if the valid password is keyed in. In order to create user friendly environment, a LCD display is connected to the system.